Analysis of Grammatical Cohesion in The Russia-Ukraine War News Text - Sahreebanu, Dhea Syahzana (Journal of Literature, Linguistics, & Cultural Studies, 2023)
Grammatical cohesion is research that analyzes how each word, phrase, or sentence is connected in a text. The researcher conducted this study to identify the types of grammatical cohesion and know how these types work in news texts. Researchers chose to use a qualitative descriptive approach in conducting this research. The data source in this study is an online news text published on Wednesday, 19 October 2022, by The Jakarta Post entitled "Russia Bombs Cities Across Ukraine at Rush Hour in Apparent Revenge Strikes." To examine the news text, researchers used the theory of grammatical cohesion developed by Cutting (2002). After conducting the analysis, the researcher found thirty-five (35) forms of grammatical cohesion out of the thirty-three (33) datums found in news texts. Of the total findings, thirty-two (32) are reference forms, and the remaining three (3) are ellipsis types. On the other hand, substitution is not found in the war news text. The type of reference most often used is the endophora in the form of anaphora (13), followed by exophora (10), associative endophora (7), and endophora in the form of cataphora (2). From these findings, each type of grammatical cohesion has its role in the news text. The reference type works as a tool to refer to a reference point in the text. Meanwhile, the ellipsis type works as a tool to remove words or phrases that are deemed unnecessary. Even so, both types of grammatical cohesion function to avoid word repetition.